IDENTIFIKASI JAMUR Candida albicans PADA URINE WANITA MENOPAUSE DI BANJAR TAMAN DESA DARMASABA KECAMATAN ABIANSEMAL KABUPATEN BADUNG - nyoman mastra (Meditory : The Journal of Medical Laboratory, 2020)
ABSTRACTBackground: menopausal women are a predisposing factor for candidiasis. In menopausal women humoral changes occur in the body and pH in the vagina. This change in pH can lead to increased fungal growth of Candida albicans. Purpose: this study aims to identify the fungus Candida albicans in urine samples of menopausal women at Banjar Taman, Darmasaba Village, Abiansemal District, Badung Regency. Method: this research was conducted descriptively with a cross sectional approach. The sampling technique with Non-probality sampling is Purposive Sampling. Urine samples were cultured on SDA media. Result: the growing colonies were identified macroscopically and microscopically and tested germ tube. Identification results showed that from 33 urine samples, 5 (15%) were positive, there was a Candida albicans fungus which showed protruding from the surface of the media, the surface on the colonies was smooth, yellowish white, and had a yeast odor. On microscopic examination it was found that yeast, pseudohifa, clamidospora, blastospora and germ tube. Conclusion: the percentage value shows the occurrence of Candida albicans fungi in the urine of menopausal women in Banjar Taman, Darmasaba Village, Abiansemal Subdistrict, Badung Regency so that menopausal women are expected to always maintain personal hygiene and routinely conduct microbiological examinations.Keywords: urine, menopausal women, candida albicans